2017
DOI: 10.1016/j.puhe.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the five-year Bloomberg Philanthropies Global Road Safety Program in the Russian Federation

Abstract: Road traffic injuries are a leading cause of morbidity and mortality in the world. In Russia, a road safety program was implemented in Lipetskaya and Ivanovskaya oblasts (regions) as part of a 10-country effort funded by Bloomberg Philanthropies. The program was focused on increasing seat belt and child restraint use and reducing speeding. The primary goals of this monitoring and evaluation study are to assess trends in seat belt use, child restraint use, and speed compliance in the two oblasts over the 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Studies from other low-income countries have shown that road safety programs which combine policy, enforcement, education and advocacy can be effective in increasing the rate of both seatbelt and child restraint usage. In Lipetskaya, child restraint usage increased from 20.9% to 51.4% from baseline to four years after program implementation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other low-income countries have shown that road safety programs which combine policy, enforcement, education and advocacy can be effective in increasing the rate of both seatbelt and child restraint usage. In Lipetskaya, child restraint usage increased from 20.9% to 51.4% from baseline to four years after program implementation [44].…”
Section: Discussionmentioning
confidence: 99%
“…The RS-10 initiative is funded by the Bloomberg Foundation and the participating countries' own resources, and is coordinated globally by the World Health Organization and its regional agencies. The objective of RS-10 was to support the governments of low-and middle-income countries to incorporate road safety measures into their national policies, thus contributing to reducing the magnitude of RTI [7][8][9][10]. Despite the differences among the countries, RS-10 activities include the safety of drivers, motorcyclists, cyclists, and pedestrians, through legislation change and enforcement; health education actions in traffic; training of police and/or public health officials to implement and monitor the impact of the initiative; improvement of databases related to RTI and its risk factors; identification of determinants for RTI and deaths; carrying out periodic inspections of alcohol and driving and excessive and/or inappropriate speed; holding selected public events and media strategies to disseminate the dangers of alcohol, incentives in the purchase of blood alcohol and over speed monitoring equipment, among others.…”
Section: Introductionmentioning
confidence: 99%
“…There is a gap in the literature on the impacts of PLT and NDL on the prevalence of driving under the influence of alcohol. International studies evaluating the PLT focused on the analysis of final indicators, such as the mortality rate and hospitalization for RTI, or other intermediate indicators, such as seat belt use and over speed driving [10,17]. In Brazil, only one study was identified that analyzed the impacts of PLT in five Brazilian cities, showing a reduction in the mortality rate indicators in three and in the prevalence of drivers with positive BAC in two [11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to assess the benefits of these interventions, a range of observational site-based evaluations have also been funded under the program. Evaluation has shown reductions in risk factors in speeding and increased seatbelt and child-restraint use in regions of Russia [ 36 , 46 ]; an increase in helmet use in provinces of Viet Nam [ 42 ]; and an increase in seatbelt use but uneven improvements in speeding in the provinces of Turkey [ 47 ]. Evaluations at the city level have shown a decrease in the prevalence of drink driving and speeding in China [ 19 ].…”
Section: Introductionmentioning
confidence: 99%